"Banking Deserts, " Bank Branch Losses, and Neighborhood Socioeconomic Characteristics in the City of Chicago: A Spatial and Statistical Analysis. Issue 2 (2nd April 2020) - Hegerty, Scott W.
Abstract : Because banks have the potential to bring a variety of benefits to their surrounding neighborhoods, the (often poor) areas that lack them can face even stronger economic challenges. These "banking deserts" might also face reputational costs if they are perceived to lack sufficient wealth or be otherwise unworthy of investment. This study examines bank locations in Chicago in 2018, establishing a set of criteria to identify areas with insufficient bank access. These block groups are shown to be poorer and less white than the city average. Econometric estimation shows that the percentage of block groups' black and, to a lesser degree, Hispanic populations is negatively related to the number of banks, even when controlling for income. Comparing these findings with bank locations in 2008, this study finds surprisingly little variation in geographic distribution, even though the total number of banks in Chicago fell by more than one fourth. This suggests that limitations in bank access are a persistent problem that precedes both the widespread adoption of mobile banking and the 2008 financial crisis. Key Words: banks, Chicago, geographic locations, socioeconomic characteristics, statistics.